Človek odtujen v množico: družbenokulturni diskurz Joséja Ortege y Gasseta - Sruk, Vida (University of Maribor Press, 2007)
Man is Alienated Into the Crowd: the socio-cultural discourse of José Ortega y Gasset. No abstract.